Development Strategy of Bekasi Creative Hub (BCH) when Developing Bekasi City’s Creative Economy - Mabrur, Yusuf; Sarma, Ma’mun; Baga, Lukman M. (JURNAL MANAJEMEN AGRIBISNIS; Vol 11 No 01 (2023): Jurnal Managemen AgribisnisDO - 10.24843/JMA.2023.v11.i01.p16, 2023)
Bekasi City is currently developing a creative economy for increase the regional economy. That’s thing stated in Bekasi City’s Rencana Pembangunan Jangka Menengah Daerah (RPJMD) 2018-2023 which reads the creative economy development based on community. The Object of this research is Bekasi Creative Hub (BCH) which is an independent organization and community that helps develop Bekasi City’s creative economy. This study aims to formulate a development strategy for BCH. Combination of Strength, Weakness, Opportunities, Threats (SWOT) and Social Enterprise Model Canvas (SEMC) methods will be used to identify the factors that might affect for BCH when developing Bekasi City’s creative economy. Internal Factors Evaluation (IFE) matrix will be used to analyze the internal factors, while the External Factors Evaluation (EFE) matrix will be used to analyze the factors. The results of the IFE and EFE matrices will be reprocessed with the IE (Internal External) matrix. The aim is to determine the condition of BCH. Based on the results of IFE and EFE matrices, BCH is in cell V which means BCH in a defend posisiton. After analyzed the factors, this research will formulate the alternative strategy for BCH with SWOT matrices methode. The results of this study, there’s nine alternative strategy for BCH to development the Bekasi City’s creative economy. The results of this study are expected to provide an overview for the Bekasi City Government in determining policies regarding the development Bekasi City’s creative economy.